Like the wind : a novel [large type] - Hatcher, Robin Lee (Thorndike Press, a part of Gale, a Cengage Company, 2022)
Olivia Ward arrived in Bethlehem Springs alone--with no job, no home, and no money--after her manipulative ex-husband used his power and wealth to destroy everything. Six years later, the peaceful life she rebuilt is once again turned upside down when she learns that her fifteen-year-old daughter, Emma, will be coming to live with her. The reunion should be a dream come true, but years of deception have driven a wedge between them. And Emma seems more interested in an old diary she discovered than reconciliation with her mother. Tyler Murphy knows what it's like to lose everything. Propelled by his history in the foster-care system, he's determined to root out dishonesty and protect the most vulnerable through his work as an investigator. When he's hired to investigate Olivia Ward, though, he finds himself longing to believe she's exactly who she appears to be, and he soon realizes that his desire to learn more about her has nothing to do with his job. But how can he pursue a relationship that began with a lie?